HPV-Related Oropharyngeal Cancer and Biomarkers Based on Epigenetics and Microbiome Profile - Gougousis, Spyridon; Mouchtaropoulou, Evangelia; Besli, Ioanna; Vrochidis, Paraskevas; Skoumpas, Ioannis; Constantinidis, Ioannis (Frontiers in Cell and Developmental Biology, 2021)
Ηuman papillomavirus (HPV) is considered the main cause of the increasing incidence rates of squamous cell carcinoma (OPSCC), and soon, the global burden of HPV related OPSCC is predicted to exceed that of cervical cancer. Moreover, a different molecular profile for HPV-related OPSCC has been described, opening new promising targeted therapies and immunotherapy approaches. Epigenetic and microbiome-based exploration of biomarkers has gained growing interest with a view to the primary oropharyngeal cancer screening. Understanding the role of the epigenetic mechanism and the changes that occur during pathogenesis shows appreciable progress in recent years. The different methylation status of DNA and miRNAs demonstrates the value of possible biomarkers discriminating even in different stages of dysplasia. Through whole-genome bisulfite sequencing, differentially methylated regions (DMR) hold the key to recover missing information. Diversely, preliminary steps of the microbiome flora investigation, drive research to given directions. Along with known co-factors playing a major role in microbiota differentiation, also HPV-related cases must be explored further to better understanding. The dynamic approach of the shotgun metagenomic sequencing will robustly fill the gap especially in species/strain level and consequently to biomarker detection. The constantly growing incidence of HPV-related oropharyngeal cancer should lead us in further investigation and understanding of the unique features of the disease, more accurate diagnostics methods along with the development and implementation of new, targeted therapies. This paper comprehensively reviews the significance of biomarkers based on epigenetics and microbiome profile in the accuracy of the diagnosis of the HPV related cancer in the oropharynx.